A Modified Model to Calculate the Size of the Crushed Zone around a Blast-Hole - Z. Leng (The Southern African Institute of Mining and Metallurgy, 2016)
"After detonation of the explosive, the final blast-induced damage area around the blast-hole falls into three categories, namely crushed zone, fractured zone, and elastic deformation zone. This paper presents a modified model to calculate the size of crushed zone around a blast-hole in drill-and-blast, with the hoop compressive stress and cavity expansion effect taken into account. The material in the crushed zone was assumed to be a granular medium without cohesion, but with internal friction. On this basis, the formula for crushing zone radius was derived. The proposed approach was verified with tests reported in the literature and the simulated results from SPH-FEM coupled models. A full statistical analysis was also carried out, and the predicted values were found to be in better agreement with the test results compared with other models. A sensitivity analysis of the modified model showed that the size of the blast-induced damage area is mainly affected by the following factors: rock mass properties, in situ stress, and borehole pressure. In particular, the roles of borehole pressure and in situ stress are discussed. Finally, suggestions are made on how the size of the crushing zones can be decreased. IntroductionOver the past decades, drill-and-blast has become the most commonly used technology in rock excavation. It is well known that in rock mass fragmentation with explosives, the annular rocks around the blast-hole are converted into fines. The formation of these fines consumes a significant part of the energy of the detonation, which in general is ignored in the determination of the efficiency of detonation (Glatolenkov and Ivanov, 1992; Furtney et al., 2012). Many studies show that only 20–30% of the total explosive energy is effectively used in fragmenting the rock, and up to 50% of the energy generated by conventional charges is wasted in overcrushing of the crushed zone and the inner part of the fractured zone (Ouchterlony et al., 2004; Sanchidrian et al., 2007). How to control the crushed zone to enhance the effective utilization of explosive energy, reducing the unit explosive consumption and the engineering cost, is therefore of great significance."